Changes in Bimanual Coordination During the First 6 Weeks After Moderate Hemiparetic Stroke. (March 2013) - Metrot, Julien; Mottet, Denis; Hauret, Isabelle; van Dokkum, Liesjet; Bonnin-Koang, Huei-Yune; Torre, Kjerstin; Laffont, Isabelle
Background . Better understanding of how bimanual coordination changes over the first weeks of recovery after stroke is required to address the potential utility for bimanual rehabilitation. Three-dimensional kinematic analysis can provide quantitative assessment of unimanual and bimanual movements. Objective . To assess the natural evolution of reaching kinematics during standard poststroke rehabilitation, focusing on bimanual coordination. Methods . A total of 12 hemiparetic, moderately impaired patients were included within 30 days after a first unilateral ischemic/hemorrhagic stroke; 7 kinematic assessments were performed once a week for 6 weeks and at 3 months after inclusion. The reach-to-grasp task was performed in 3 different conditions: unimanual with the healthy limb (UN), unimanual with the paretic limb (UP), and bimanual (BN/BP). Results . For the paretic limb, movement fluency (number of movement units and total movement time) was lower for bimanual reaching compared with unimanual reaching. For bimanual reaching, (1) movement kinematics were similar for both limbs, (2) recovery patterns of both limbs followed a similar profile with a plateau phase at 6 weeks poststroke, and (3) intertrial variability of between-hands synchronization decreased over sessions, although the mean delays remained the same. Conclusions . Bimanual coordination started to become efficient 6 weeks after onset of stroke, so for patients such as those we tested, this time could be most opportune to start bimanual-oriented rehabilitation. The challenge in future research includes determining the characteristics of patients who may best benefit from bimanual therapy.